2015
DOI: 10.1002/qre.1953
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis Method on Repairable System with Standby Structure Based on Goal Oriented Methodology

Abstract: a This paper presents a reliability analysis method on repairable system with standby structure based on goal oriented (GO) methodology. Firstly, a new combination of GO operator, which is composed of a new logical GO operator named Type 18A operator and a new auxiliary GO operator named Type 20 operator, is created to represent standby mode. The availability formula of standby equipment with translation exception is deduced based on Markov process theory. Then, the application method of combination of GO oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 12 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…However, the Type 18 operator requires that the primary equipment and the standby equipment are input units. Thus, Yi et al created a new function operator, named Type 18A operator, and a new logical operator, named Type 20 operator, to overcome the limitations of Type 18, as shown in Figure B. In order to conduct effective reliability analysis of multistate systems, Type 3 operator and Type 15 operator are redefined and applied to the reliability analysis of a pyrotechnics system .…”
Section: Development Of the Theory Of The Go Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Type 18 operator requires that the primary equipment and the standby equipment are input units. Thus, Yi et al created a new function operator, named Type 18A operator, and a new logical operator, named Type 20 operator, to overcome the limitations of Type 18, as shown in Figure B. In order to conduct effective reliability analysis of multistate systems, Type 3 operator and Type 15 operator are redefined and applied to the reliability analysis of a pyrotechnics system .…”
Section: Development Of the Theory Of The Go Methodsmentioning
confidence: 99%
“…Compared with the above two direct GO algorithms and three GO algorithms with shared signal from aspects of operation accuracy, operation efficiency, applicability, and operability, the results are presented in Table . Reliability analysis of several engineering systems with shared signals has revealed that the exact algorithm above is the best choice for complex systems …”
Section: Development Of the Theory Of The Go Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the GO method has also been applied in the reliability analysis of defense systems, water, oil, and gas supply systems, manufacturing systems, transportation systems, power systems, and logistics management systems [2,3]. Furthermore, the theory of GO method for a complex system with complex correlations (dependencies), closed-loop feedback, multiple functions, multiple fault modes, etc., has been developed from three aspects, which are GO model, basic GO algorithm, and GO method for complex systems with various characteristics [9][10][11][12][13][14][15][16][17]. Literature [2,3] gave the overview of development of GO method in detail.…”
Section: Development Of Go Methodsmentioning
confidence: 99%
“…The existing 17 basic GO operators in the GO method were not sufficient to describe the standby relationship between the primary equipment and standby equipment, so Shen et al created the Type 18 operator based on Markov process theory to address this problem . The Type 18 operator still has some limitations, so Yi et al presented a reliability analysis method for a repairable system with a standby structure based on the GO method to overcome this problem . In order to conduct an effective reliability analysis for a system with multiple states, Zhou et al redefined the Type 3 operator to describe 3 states for the main charge of the retracting actuator and improved the Type 15 operator to describe the logic relations of the multi‐state output, and Yi et al created a new function GO operator named Type 19 operator to describe the unit turning unstable operation into normal operating .…”
Section: Introductionmentioning
confidence: 99%